Physical functioning and risk for sleep disorders in US adults: results from the National Health and Nutrition Examination Survey 2005–2014. (November 2017) - Puri, S.; Herrick, J.E.; Collins, J.P.; Aldhahi, M.; Baattaiah, B.
Abstract: Objectives: Sleep disorders (SDs), particularly problems with falling asleep or daytime sleepiness, have negative impact on health and longevity. Sleep deprivation is also associated with a decline in physical functioning (PF) that mediates the ability to perform activities of daily living. But it remains unknown if deterioration in PF can predict the risk of having a SD. Therefore, the purpose of the present study is to assess the risk of SD associated with PF status in the US adult population. Study design: Cross-sectional study design with data from the National Health and Nutrition Examination Survey from year 2005 to year 2014. Methods: PF limitation is assessed by reported difficulty in performing 10 tasks selected from PF questionnaire. SD is identified by subjective description of presence of doctor diagnosed SD. Also, five categories of comorbidities that caused difficulty in carrying out these tasks were created. Results: The adults with self-reported PF limitation have 41% higher odds of having a SD (odds ratio [OR] = 1.41, 95% confidence interval [CI] = 1.22–1.59). Moreover, participants having cognitive problems and cardiovascular and pulmonary disorders as secondary conditions that cause difficulty in PF have 145% and 28% higher odds (OR = 2.45 and 1.28; 95% CI = 2.01–3.01 and 1.08–1.53, respectively) of having a SD. Also, females have a 27% lower odds of having a SD than males (OR = 0.73, 95% CI = 0.63–0.83). Conclusion: Risk for SD is associated with increasing level of functional disability. We advocate the importance of engagement in physical activities to prevent or delay the onset of SD. Highlights: Sleep and physical functioning are associated. Patients with significant functional disability should be screened for sleep disorders. Adults with cognitive and cardiovascular dysfunction are at greater risk for being diagnosed with a sleep disorder. Men with functional disability are at greater odds of being diagnosed with a sleep disorder when compared to women.